Beneficiation of ceramic raw materials in Ghana: Composition of samples of clay materials (Journal of Science and Technology, 2016)
Study of the mineralogy, chemical composition, and physical characteristics of clays from selected clay deposits in Ghana was made. Appraisal of data obtained from this study testifies to the appropriate usage of these clays for ceramic products development.